2006
DOI: 10.1088/0031-9155/51/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating microcirculation by pulsatile laser Doppler signal

Abstract: Laser Doppler flowmetry (LDF) is a popular method for monitoring the microcirculation, but it does not provide absolute measurements. Instead, the mean flux response or energy distribution in the frequency domain is generally compared before and after stimulus. Using the heartbeat as a trigger, we investigated whether the relation between pressure and flux can be used to discriminate different microcirculatory conditions. We propose the following three pulsatile indices for evaluating the microcirculation cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…Many previous studies found that changes in the elastic properties of the MVBs influenced arterial wave transmission [34, 39]. Since the arterial BP was suggested to be an important driving force pushing the MBF into tissues through arteriolar openings [17, 20], the whole-body distribution of the microcirculatory blood perfusion might be altered. Many treatment methods in Asian traditional medicine, such as Chinese herbs and acupuncture, have been noted to influence arterial wave transmission [40, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies found that changes in the elastic properties of the MVBs influenced arterial wave transmission [34, 39]. Since the arterial BP was suggested to be an important driving force pushing the MBF into tissues through arteriolar openings [17, 20], the whole-body distribution of the microcirculatory blood perfusion might be altered. Many treatment methods in Asian traditional medicine, such as Chinese herbs and acupuncture, have been noted to influence arterial wave transmission [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were asked to relax and breathe naturally throughout the measurement period so as to avoid motion artifacts. The signals were connected to an analog-to-digital converter card (PCI-9111DG, Adlink Technology, Taiwan) operating at a sampling rate of 1024 Hz [1720]. …”
Section: Methodsmentioning
confidence: 99%
“…To determine the parameters from the pulsatile LDF waveform, the LDF flux signal was first filtered by a digital high-pass filter (11th-order Chebyshev filter) with a cut-off frequency of 0.01 Hz to eliminate baseline drift. Then, a time-domain synchronized to average in a similar range to those of our previous works 18,19 was performed to enhance the pulsatile component of the LDF flux. We first identified the cardiac component of each ''pulse'' of the microcirculatory flux according to the neighboring two R-peaks, and then we cut the LDF flux wave at the same cut point.…”
Section: Discussionmentioning
confidence: 99%
“…It can be appreciated the peaks of LDF signal appeared synchronously correlated with the R-peaks of ECG signal after a certain phase delay. In order to determine the length of the LDF signal of each beat, the “beat-to-beat” algorithm was applied [1517]. According to this algorithm, the “waveform” of LDF signals in heart-beat frequency was derived.…”
Section: Methodsmentioning
confidence: 99%
“…Since the microvascular perfusion function may be associated with muscle flexibility, the aim of this study is to develop convenient indices for the assessment of muscle flexibility by analyzing the characteristics of blood perfusion determined by non-invasive LDF technique during different muscle stretching and relaxed states. After the signal processing with the modified beat-to-beat algorithm [15,16], the flexibility indices can be defined in participants with different flexibility levels of calf muscle.…”
Section: Introductionmentioning
confidence: 99%